Exposure to low environmental copper concentrations does not affect survival and development in Atlantic cod (Gadus morhua) early life stages. (2021) - Farkas, Julia; Svendheim, Linn H.; Jager, Tjalling; Ciesielski, Tomasz M.; Nordtug, Trond; Kvæstad, Bjarne; Hansen, Bjørn H.; Kristensen, Torstein; Altin, Dag; Olsvik, Pål A.
Graphical abstract: Highlights: Early life stages of cod were exposed to environmentally relevant Cu concentrations. Copper significantly accumulated in eggs but not in larvae. Exposure to the tested Cu concentrations did not increase mortality or deformations. Low Cu exposure did not affect development and growth of cod early life stages. Abstract: In this study we investigated potential impacts of Cu exposure at low, environmentally relevant, concentrations on early live stages of Atlantic cod ( Gadus morhua ). Cod embryos and larvae were exposed to 0.5 μg/L (low), 2 μg/L (medium), and 6 μg/L (high) Cu from 4 to 17 days post fertilisation (dpf). Hatching success, mortality, oxygen consumption, biometric traits, and malformations were determined. A dynamic energy budget (DEB) model was applied to identify potential impacts on bioenergetics. A positive correlation was found between Cu exposure concentrations and Cu body burden in eggs, but not in larvae. The tested concentrations did not increase mortality in neither embryos nor larvae, or larvae deformations. Further, the DEB model did not indicate effects of the tested Cu concentrations.